Incomes policy and capital sharing in Europe - Robinson, Derek (New York : Barnes & Noble Books, 1973)
This books deal with incomes policies; provision of wealth assets for employed persons; report of trade union experts on the general subject of capital-sharing and the report of a multinational study group to the Federal Republic of Germany.
Includes bibliographical references and index.
osa 03/08/17
Loans
Keywords: Income; Wage-price policy; Profit-sharing.; Collective bargaining